PENGHILANGAN BAU AMONIAK DARI TEMPAT PENUMPUKAN LEUM PADA INDUSTRI KARET REMAH DENGAN MENGGUNAKAN TEKNIK BIOFILTER - Mohamad Yani; . Purwoko; Andes Ismayana; Puji Rahmawati Nurcahyani; Derin Pahlevi (Institut Pertanian Bogor, 2012)
Malodorous gases emitted from natural rubber industries. At crumb rubber plant, leum storage emits high concentration of ammonia that strength odor and dangerous to healthy workers. This research occurred to remove ammonia from leum storage using biofilter coloum 23L packed with mixed of top-soil, peat-rubber leaves and sludge. The result shows that this biofilters can remove ammonia from inlet concentration at 4 - 20 ppm to outlet concentration less than 4,7 ppm (average of 1,1ppm below regulation limit of 2 ppm). The biofilter packed with top soil performs to ammonia removal efficiency average of 89% and ammonia-removal capacity at 0,36 g-N/kg-dry-material/d. The biofilter packed with mixed of top soil and rubber leaves performs to ammonia removal efficiency average of 85% and ammonia-removal capacity at 0,60 g-N/kg-dry-material/d. The biofilter packed with mixed of top soil and sludge performs to ammonia removal efficiency of 99% and ammonia-removal capacity at 0,36 g-N/kg-dry-material/d. The biofilter packed with mixed of top soil and sludge indicated the most stable on ammonia removal capacity and the lowest oulet ammonia at an average of 0.1 ppm.